THE RING OF GYGES AND THE MODERN WORLD: : INVINCIBILITY THROUGH INVISIBILITY IN ORGANIZATIONAL STRUCTURES – A QUALITATIVE AND HERMENEUTICAL INTERPRETATION (Journal of European Studies (JES), 2018)
Even after 2500 years, Plato holds the distinction of being a philosopher whose described anecdotes carry everlasting stores of knowledge. This article takes an allegorical and hermeneutical approach to interpret the tale of the Ring of Gyges, which symbolizes a feature of human behaviour that when in possession of infinite power people often become invisible, and so choose to violate norms of morality for the sake of pleasure. The research tries to elaborate how invisibility at the workplace drives certain individuals towards corruption. The lust for invisibility is due to the fact that an undying spirit of competition is infiltrated at the grass-root level, which has engendered, amongst all rational individuals, the need to possess power by whatever means available. It is power that affords individuals the luxury of being invisible to the watchful eyes of observers and escape punishment even for severe crimes.
Keywords: Power Politics; Capitalism; Organizational Invincibility; Ring of Gyges; Invisibility